Scratching the surface: biomarkers and neurobiomarkers for improved allergic contact dermatitis management - Sasaki, Akimi; Sargen, Manuel; Maskey, Anish R.; Li, Xiu-Min (Frontiers in Allergy, 2025)
Allergic contact dermatitis (ACD), also known as allergic eczema, is a common inflammatory skin disorder that affects millions of Americans and imposes significant physical, psychological, and economic burdens. Differentiating ACD from other forms of dermatitis remains a challenge, with patch testing as the gold standard. Despite its utility, patch testing can lack diagnostic accuracy, highlighting the importance of molecular biomarkers to refine diagnosis and treatment. Advances in transcriptomics and machine-learning have enabled the identification of biomarkers involved in ACD, such as loricrin (LOR), ADAM8, CD47, BATF, SELE, and IL-37. Moreover, biomarkers such as LOR, NMF, and TEWL, may have prognostic value in evaluating therapeutic response. Emerging neurological biomarkers (neurobiomarkers), including IL-31 and TRPV1, target pathways involved in the pruritic and inflammatory responses, offering novel therapeutic targets as well. This mini review summarizes current ACD treatments, biomarkers for targeted therapies, and emphasizes the role of neurobiomarkers in ACD treatment. Additional research on the validity of the therapeutic potential of these biomarkers is necessary to improve ACD treatment and outcomes.